2015
DOI: 10.1097/md.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglyceride Levels Independently Contribute to the Estimation of Visceral Fat Amount Among Nondiabetic Obese Adults

Abstract: Determining the visceral fat amount is important in the risk stratification for the prevention of type 2 diabetes and obesity-related disorders. The area-based measurement of visceral fat area (VFA) via magnetic resonance imaging (MRI) is an accurate but expensive and time-consuming method for estimating visceral fat amount. The aim of our study was to identify a practical predictive parameter for visceral obesity in clinical settings.In this cross-sectional study, we recruited 51 nondiabetic obese (body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
2
15
0
2
Order By: Relevance
“…Policosanol consumption reduced the TG/HDL-C ratio and visceral fat amount ( Table 1 ). In the current study, reduction of serum TG level was correlated with reduction of visceral fat mass in the policosanol group, and a Taiwanese study revealed that the serum TG level independently contributes to visceral fat amount [ 44 ]. Reduction of serum TG level could cause reduction of visceral fat mass.…”
Section: Discussionmentioning
confidence: 98%
“…Policosanol consumption reduced the TG/HDL-C ratio and visceral fat amount ( Table 1 ). In the current study, reduction of serum TG level was correlated with reduction of visceral fat mass in the policosanol group, and a Taiwanese study revealed that the serum TG level independently contributes to visceral fat amount [ 44 ]. Reduction of serum TG level could cause reduction of visceral fat mass.…”
Section: Discussionmentioning
confidence: 98%
“…TAG as precursors of signaling molecules, including long-chain fatty acyl-coenzyme A, diacylglycerols, and ceramides, impair insulin signaling and secretion and, hence, glucose uptake. Additionally, VAT has been previously associated with concentrations of TAG in healthy Chinese individuals with normoglycemia and obesity (41), which is suggested to be the result of increased lipolysis due to the combination of increased production of TAG and their impaired clearance. Consistent with these outcomes, concentrations of both VAT and TAG were strong predictors of FPG in Chinese, and Caucasian, individuals.…”
Section: Original Articlementioning
confidence: 99%
“…The decreased visceral adiposity and possibly subsequent changes in liver lipid metabolism might have contributed to this tendency. In fact, hypertriglyceridaemia has been demonstrated to be the only independent correlate of visceral adiposity among several biometric and metabolic parameters in obese humans …”
Section: Discussionmentioning
confidence: 99%